"Visions don't work"? The role of Wesker's theatre and Centre 42 in 1960s' British culture. Issue 2 (3rd May 2016) - Etienne, Anne
Abstract: Undeterred by Dave's conclusion that 'Visions don't work', Ronnie Kahn, in I'm Talking About Jerusalem, responds: 'They do work! And even if they don't work then […] let's try and behave as though they do – or nothing else will work' (216). This vindication of the need to follow visions resonates with an optimism that very much characterises the spirit of the 1960s. It also points to the notions of attempts and experimentation, an apt angle through which Wesker's work in the sixties and beyond ought to be considered anew. In the post-reconstruction period, the theatrical renaissance was a space for aesthetic and cultural attempts, however ill-defined, and Wesker became a major figure in redefining a role and a place for the arts. However, both C42 and the plays he wrote at the time failed, taking down his reputation, his audience, his critical following and quite a few friends. Based on archival research, this article explores Wesker's work in the sixties by interrogating the generalised conclusion that C42 was a failure that also finished him as a playwright. The interdisciplinary approach looks at the dialectics between his stage work and his cultural venture and reassesses the importance of Wesker's visions.